Validity and Practicality of Digital Student Songbook as Supporting Thematic Teaching Material in Elementary School - Desyandri, Desyandri; Yeni, Indra; Mansurdin, Mansurdin; Dilfa, Alrizka Hairi (Jurnal Ilmiah Sekolah Dasar, 2021)
The industrial revolution 4.0 and 21st-century skills leave fundamental problems in the implementation of 2013 curriculum teaching materials with an integrated thematic approach, including learning the art of music in elementary schools. It is very important for teachers to integrate technology into learning. The purpose of this research is to develop interactive multimedia in the form of a digital songbook as a support for integrated thematic teaching materials. The type of research that has been used is Research & Development which refers to the ADDIE process: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The subjects of this study were 4 (four) teachers and 100 elementary school students in the city of Padang. Data collection techniques and instruments were in the form of a questionnaire consisting of a validation questionnaire for validators and a practicality questionnaire given to teachers and students. The data analysis technique was obtained by taking the average results of product validation and practicality. The results showed that the average score of content and graphic validation was 84.1% in the appropriate category, while the average practicality score was 86.7%. Thus, the Digital Song Book is feasible and practical to use in learning the art of music as a support for integrated thematic teaching materials in elementary schools that meaningful for elementary students. The findings of this study have significant implications for designers and teachers, as well as multimedia researchers.Â